Aberrant expression of miR-153 is associated with the poor prognosis of cervical cancer - Liu, Li (Oncol Lett, 2018)
Previous studies have demonstrated that microRNAs (miRNAs) are frequently dysregulated in tumors and are associated with the initiation and progression of various types of cancer. miR-153 has been previously shown to have an anti-tumor effect in the majority of cancer types. However, to date, the expression status and function of miR-153 in cervical cancer (CC) remains unclear. In the present study, the expression of miR-153 in CC tissues and cell lines was examined, revealing that the expression of miR-153 was markedly downregulated in the CC tissues and cell lines investigated, when compared with matched noncancerous tissues and normal cervical epithelial cell line. Furthermore, ectopic expression of miR-153 by miR-153 mimic inhibited cell proliferation; however, transfection with the miR-153 inhibitor promoted the cell proliferation in CC cell lines. Finally, the results showed that the downregulation of miR-153 was associated with poor 5-year over survival in CC patients and it could be regarded as an independent biomarker to predict the prognosis of CC patients. Collectively, these results indicated that miR-153 may function as a tumor suppressor in CC, and it may be a potential novel therapeutic target for CC.